The ergogenic effects of supplemental nutritional aids on anaerobic performance in female athletes. - Glenn, J. M.; Gray, M.; Gualano, B.; Roschel, H. (Strength and Conditioning Journal, 2016)
Athletes are constantly searching for methods with which to increase athletic performance. The use of ergogenic aids is popular among athletes; however, most research is collected in male subjects. Based on physiological and morphological differences between genders, it cannot be assumed women will demonstrate similar responses as men. Sixty-five percent of female athletes report use of ergogenic aids and it is imperative to evaluate female-specific benefits. This review presents the current literature evaluating effects of ergogenic aids on anaerobic performance in women and recommendations for use. For a video abstract of this article see supplemental digital content 1,